Audit quality across non-audit service fee benchmarks: Evidence from material weakness opinions. Issue 2 (October 2017) - Legoria, Joseph; Rosa, Gina; Soileau, Jared S.
Abstract: Regulators have voiced concerns regarding the impact of auditor provided non-audit services (NAS) on auditor independence, and by extension, audit quality. This study considers whether the provision of various levels of (NAS) influences the auditor's propensity to issue material weakness opinions (MWO). The results indicate that audit clients that purchase zero NAS, and clients that purchase NAS less than Sarbanes-Oxley's benchmark of NAS fees less than 5% of total fees, are more likely to receive a MWO than clients with a NAS at higher levels.